Effect of acquittal on the humanization of criminal policy in criminal proceedings (Journal of actual problems of jurisprudence, 2018)
The article deals with some issues the influence of acquittals on humanization of criminal policy in the criminal trial of RK. The author shows the data of foreign practice, historical statistical facts about the number of acquittal, as well as contemporary problematic issues that arise in the judgment of acquittal and after its issuance. The author argues that one of the hallmarks of democratic justice is the percentage of the number of acquittals, decides courts, in their relation to the number of convictions.Key words: acquittal, criminal justice, the grounds acquittal, the defense, the prosecution, defense, appeal, protest.